Development of an Interactive E-Module Containing Gamification on the Material of Relations and Functions - Erawati, Ni Ketut; Yuliastini , Ni Kadek; Juwana , I Dewa Putu (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research is motivated by the low motivation and learning outcomes of students in the topic of Relations and Functions, as well as the limited use of technology-based teaching materials at SMP Negeri 2 Mengwi. The purpose of this study is to develop an interactive e-module with gamification and to test its validity, practicality, and effectiveness. The research employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The product was validated by two experts, while trials included both limited and field testing. The validation results indicated that the e-module received a score of 1.00 in both material and media aspects, categorized as very high. Practicality was measured using the User Experience Questionnaire (UEQ), with most aspects rated as “excellent.” In terms of effectiveness, students’ learning motivation was in the very high category with an average score of 83, and the average learning outcomes increased from 68 to 84 after using the e-module. Therefore, the interactive e-module with gamification is considered valid, practical, and effective for use in mathematics learning on the topic of Relations and Functions.